TRANSMISI KEILMUAN PADA ERA MILENIAL MELALUI TRADISI SANADAN DI PONDOK PESANTREN AL-HASANIYAH - Ahmad Suhendra (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The process of knowledge transmission in boarding school (pesantren) is done by maintaining tradition of giving ‘ijazah sanad’ (license on chain of transmission) . It enables that the teaching delivered in Pesantren continued to the authors of book (kitab) up to prophet Muhammad (peace be upon him). In millennial era today, some people study about religion to unclear teacher. They learn through social media, such as Facebook and YouTube. People are easily to access cross-regional studies. However, in millennial life, one of pesantren in Tangerang still maintains sanadan tradition. Pondok pesantren Al-Hasaniyah used to hold sanadan at the end of the year. This article explains the urgency of sanad for scholarship in the millennial era and describes the sanadan tradition in the Pesantren al-Hasaniyah in the transmission of religious knowledge. This study uses qualitative approach and data collected through observations and interviews. This results found that Pondok Pesantren Al-Hasaniyah formalizes sanadan tradition into an annual agenda so that students have a clear knowledge and connected until prophet Muhammad saw. However, it needs innovation in order to continuosly exist and not only for annual rituals.